2020
DOI: 10.1016/j.envres.2020.109754
|View full text |Cite
|
Sign up to set email alerts
|

SARS-Cov-2RNA found on particulate matter of Bergamo in Northern Italy: First evidence

Abstract: Background: The burden of COVID-19 was extremely severe in Northern Italy, an area characterized by high concentrations of particulate matter (PM), which is known to negatively affect human health. Consistently with evidence already available for other viruses, we initially hypothesized the possibility of SARS-CoV-2 presence on PM, and we performed a first experiment specifically aimed at confirming or excluding this research hyphotesys. Methods: We have collected 34 PM10 samples in Bergamo area (the epicenter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
396
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 415 publications
(412 citation statements)
references
References 13 publications
8
396
2
6
Order By: Relevance
“…Research Hypothesis . Based on the available literature, and following our recent publication confirming the presence of SARS-COV-2 RNA on PM 10 collected in Bergamo area (the epicentre of the Italian epidemic), 20 there is enough evidence to consider the airborne route—and specifically the role of PM—as a possible additional infection ‘boosting’ factor for interpreting the anomalous COVID-19 outbreaks observed in Northern Italy, known to be one of the areas characterised by the highest PM concentrations in Europe. 1 Airborne transmission is certainly more effective in indoor environments, with little ventilation, but it must be considered that the Po Valley—due to its atmospheric stability—closely resembles a confined environment, and that long-distance virus transportation is favoured by high concentration of dust.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Research Hypothesis . Based on the available literature, and following our recent publication confirming the presence of SARS-COV-2 RNA on PM 10 collected in Bergamo area (the epicentre of the Italian epidemic), 20 there is enough evidence to consider the airborne route—and specifically the role of PM—as a possible additional infection ‘boosting’ factor for interpreting the anomalous COVID-19 outbreaks observed in Northern Italy, known to be one of the areas characterised by the highest PM concentrations in Europe. 1 Airborne transmission is certainly more effective in indoor environments, with little ventilation, but it must be considered that the Po Valley—due to its atmospheric stability—closely resembles a confined environment, and that long-distance virus transportation is favoured by high concentration of dust.…”
Section: Discussionmentioning
confidence: 96%
“… 19 Recently, we have published the first evidence in the world of the presence of COVID-19 on outdoor PM in samples collected between 23 February and 9 March in the province of Bergamo (Lombardy, Italy), which experienced the highest diffusion and mortality rates in Italy. 20 A research carried out by the Harvard School of Public Health seems to confirm an association between increases in PM concentration and mortality rates due to COVID-19. 21 On March 16th 2020, we have released an official position paper highlighting that there is enough evidence to consider the airborne route as a possible additional factor for interpreting the anomalous COVID-19 outbreaks notified in Northern Italy, known to be one of the European areas characterised by the highest PM concentrations.…”
Section: Introductionmentioning
confidence: 98%
“…Although this study was occurring in medical site, some relatively unventilated spaces, such as chorale [151] , restaurant [152] , fitness [153] , have also reported the possibility of aerosol transmission. On the outdoor, the SARS-CoV-2 RNA has also been found on particulate matter in northern Italy [42] .
Fig.
…”
Section: Characteristics Of Coronaviruses In Aerosol and Inanimate Sumentioning
confidence: 95%
“…Recently, large numbers of investigations have reported that the RNA of SARS-CoV-2 has been detected in raw sewage, secondary treated wastewater (normally biological wastewater treatment process being applied), and even the non-potable water used for urban irrigation ( Fig. 2 ) [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] . More importantly, the infectious virus has also been detected in feces and urine of patients [45] , [46] , [47] , which triggered the public’s high concern about fecal-oral transmission and/or wastewater transmission.…”
Section: Introductionmentioning
confidence: 99%
“…In general, airborne infectious viruses are di cult to monitor due to their extremely low concentration in air and because of the inadequacy and lack of accuracy of currently used air samplers. Despite these di culties, the presence of SARS-CoV-2 was successfully detected on PM10 particles in a polluted area in Northern Italy in the period 21 February -13 March 2020 (Setti et al, 2020), i.e. at the time of the pandemic outbreak.…”
Section: Considerations On Inhaled Aerosol Particles and Their Potentmentioning
confidence: 99%